Analisis Konsep Pendidikan Agama Islam : Prespektif Ibnu Miskawaih Dan Ibnu Sina - Moh. Syafi’i; Moh. Zayyadi (Pascasarjana Universitas Qomaruddin, 2023)
With the flow of rational-religious philosophy, of course, thinkers in conceptualizing an education cannot escape the role of religion and reason. The leaders of the adherents of this school are Ibn Miskawaih and Ibn Sina, this research is certainly made as a starting point to see the differences between the two. This research is library . The primary data in this study is a journal about the thoughts of Ibn Miskawaih and Ibn Shina. In this study, the researcher used content analysis in a descriptive form. The results of this study are: In terms of goals, the two figures proclaimed character-based goals. Ibn Miskawaih proclaimed character-based cognitive goals, then Ibn Sina proclaimed character-based Psychomotor goals. In terms of material, both provide religious material and worldly material, but Ibn Sina is more adapting the material to be given to the psychology of students. From the aspect of the method, the two figures have similarities in providing methods, namely in providing role models and providing a good environment from an early age, but the method used by Ibn Sina focuses more on student/psychomotor skills that does not leave affective, while Ibn Miskawaih focuses on affective. which does not leave cognitive. In terms of evaluation, Ibn Miskawaih's standard provides more detailed standards for student achievement than Ibn Sina's